PENYULUHAN PENGELOLAAN SAMPAH PLASTIK PADA BANK SAMPAH SAKINAH PADANG PANJANG - Yuli Y; Jumyetti Jumyetti; Rahmi Hidayati; Rina Rina; Januar Putra (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Community service has been carried out by a team from the Padang State Polytechnic. This activity was carried out due to concerns about the large amount of inorganic household waste that had accumulated in the Guguak Malintang sub-district, Padang Panjang Timur sub- district, which had not been processed, making members of the Sakinah waste bank in the sub-district want to process it into useful materials. This desire was responded directly by the service team from the Padang State Polytechnic, so that cooperation was established in the form of a partnership. The purpose of the activity is to contribute to the application of science and technology in carrying out the tri dharma of higher education, namely the third dharma of community service. The activity took place thanks to the collaboration of the community service team from the Padang State Polytechnic with the Sakinah waste bank which is a partner. This plastic waste recycling training aims to enable participants to have the skills and entrepreneurial spirit resulting from plastic waste recycling. The method used in this activity is first to socialize about the importance of waste management, and to continue the practice of making various souvenirs from plastic waste. During the socialization, the waste bank members and community members who attended were very enthusiastic to listen to it, even the participants wanted to practice directly. It is hoped that by holding the skills to make various souvenirs of plastic waste, the environment will be maintained and the accumulation of plastic waste will not occur. The resulting souvenirs can not only be sold to increase family income, but also reduce the amount of plastic waste that is difficult to decompose.